A Global Survey of Gastroenterologists' Travel Advice to Patients with Inflammatory Bowel Disease on Immunosuppressive Agents and Management of Those Visiting Tuberculosis-Endemic Areas. (11th September 2018) - Chan, Webber; Shim, Hang Hock; Ng, Siew Chien; ,; Liu, Jeffrey; Inglis, Christian; Greveson, Kay; Baraty, Brandon; Haifer, Craig; Leong, Rupert W L
Abstract: Background: With increasing use of biological therapies and immunosuppressive agents, patients with inflammatory bowel disease[IBD] have improved clinical outcome and international travel in this group is becoming common. Adequate pre-travel advice is important. We aim to determine the proportion of gastroenterologists who provided pre-travel advice, and to assess their management strategies for patients on biological therapies visiting tuberculosis[TB]-endemic areas. Methods: A 57-question survey was distributed to IBD physicians in 23 countries. We collected physicians' demographics, and using a standardized Likert scale, assessed physicians' agreement with stated treatment choices. Results: A total of 305 gastroenterologists met inclusion criteria. Overall, 52% would discuss travel-related issues: travellers' diarrhoea [TD], travel-specific vaccines, medical care and health insurance abroad, and TB. They were more likely to advise patients not to travel to TB-endemic area if on both anti-tumour necrosis factor [TNF] and azathioprine, than if on vedolizumab and azathioprine [47% vs 17.6%, p < 0.01]. More IBD physicians agreed with vedolizumab monotherapy vs anti-TNF monotherapy [29.9% vs 23%, p < 0.01]. Two-thirds would continue all IBD treatments and not cease any medications. Chest X-ray and interferon-gamma-release assay were the preferred methods to assess for active and latent TB infection. Knowledge on vaccines among IBD physicians was inadequate (survey mean [SD] scores 10.76 [±6.8]). However, they were more familiar with the societal guidelines on management of venous thromboembolism and TD (mean scores 14.9 [±5.3] and 11.9 [±3.9] respectively). Conclusion: Half of IBD specialists would provide pre-travel advice to IBD patients and two-thirds would advise continuing all IBD medications even when travelling to TB-endemic areas. More education on vaccinations would be particularly helpful for IBD physicians.